Institutionalization of the development management system in Poland - Sługocki Waldemar (Management)
Institutionalization of the development management system in Poland The Polish development policy was shaped along with the process of political transformation and integration with the European Union. After 1990, the management of development policy had a provisional character, in fact the system did not exist. At the national level, there was certain lack of the legal framework, strategic documents, institutional framework and financing. The progressively progressing process of European integration, the transfer of pre-accession funds and the prospect of EU membership and also the possibility of implementing cohesion policy have enabled the adoption of solutions appropriate for many EU Member States. In the first phase, in 1998, exactly on 5 June, the law on voivodship and poviat level self-government was adopted. The following year, the act on departments was adopted, on the basis of which the office of the minister competent for development was established, and in 2000 the fundamental act of law was adopted, namely the act on the principles of supporting regional development. Along with the possibility of cohesion policy implementation, a strategic planning system was adopted, primarily for the purpose of taking advantage of the European funds, and the corresponding institutional set-up was created. However, it was only in 2008, at the initiative of the Strategic Advisory Group at the Prime Minister, that the solutions at that time were reviewed and changes were recommended in the area of strategic management of Poland’s development. The justification for the changes was the need to have a new “compass of development”, which after the period of implementation of accession goals and short-term needs characteristic of societies in the transformation phase prevented the so-called “development drift” situation, that is, stable growth, but too weak to compare to the most developed Western countries. After the adoption of the document “Assumptions of the development management system of Poland” by the Council of Ministers on 27 April 2009 and as a result of further work, a national development management system was developed.